Entrepreneurial behavior among front line employees in Universiti Sains Islam Malaysia (USIM) / Muhammad Asif Abdullah - Abdullah, Muhammad Asif (Faculty of Business and Management, 2010)
Nowadays, there are a less number of researches about entrepreneurial behavior among Public Servants locally. It would be beneficial and interesting to have more current research regarding this area due to the rapidly changing culture and environment in the Public Sector. The purpose of this study is to identify significant different in term of Entrepreneurial Behavior among Gender, Division, Level of Education, Length of Service in Public Sector and Length of Previous Service in Private Sector given the subject for this study is the front line employees in Universiti Sains Islam Malaysia (USIM). It is hope that the result derived from this study would enable USIM to determine the Level of Entrepreneurship among their staff. The data was obtained by using two methods which are primary data and secondary data. For primary data, respondents were asked to answers 80 sets of questionnaires to determine the Level of Entrepreneurial Behavior. The Data then analyzed using Statistical Program for Social Science (SPSS) Program. By using all 11 items in Questionnaire, the findings highlight three Entrepreneurial Behavior that comprise; Change Orientation, Strategic Vision and Energetic Working Environment. In determining the Significant Difference, a Likert-type scale has been developed and tested. The result indicates that there is no significant difference among the five personal variables towards Entrepreneurial Behavior.